Karya Seni Scribble Wajah Pahlawan Indonesia sebagai Upaya Mengingat Jasa Pahlawan terhadap Generasi Muda - Rizkyhimawan, Adhytia; Susilo, Mas Bayu; Suparti, Suparti (Jurnal Teknik Informatika dan Desain Komunikasi Visual, 2025)
Art plays a crucial role in the commemoration and historical study of a nation. This research focuses on the use of scribble technique as a medium in visual art depicting portraits of Indonesian heroes. Using qualitative methods and Narrative Analysis, the study illustrates scribble as an effective medium in fostering appreciation for heroic works and reinterpreting historical values for younger generations. Thus, scribble emerges not only as a significant expression of creativity but also as a tool for historical education, inspiring the youth. The research highlights that scribble art possesses strong visual appeal and is accessible to younger audiences. Moreover, it underscores its utility as educational material for relearning the values of heroism. In conclusion, scribble art transcends mere creative expression to function as an innovative tool for historical education. Leveraging modern artistic media, it aims to enhance awareness and appreciation among the youth towards the contributions of national heroes.